The Development of Curup from a Market-Based Settlement into an Urban Structure: An Urban Ecology Approach - Muhammad Alif Athallah; Maulid Hariri Gani; Nisbatun Nisak (Peneliti.net, 2026)
Urban development is often influenced by the interaction of economic, social, and historical factors that shape urban spatial structures. However, studies concerning the development of Curup from a market-based settlement into an urban structure remain limited and have not been extensively analyzed using the perspective of urban ecology. This study aims to analyze the development of Curup from a market-based settlement into an urban structure through the urban ecology approach proposed by Robert E. Park. The study employed a descriptive qualitative method with a case study design. Data were collected through observation, interviews, documentation, and literature review, and were subsequently analyzed using the stages of data reduction, data presentation, and conclusion drawing. The findings indicate that the market became the primary factor driving the growth of settlements and economic activities in Curup. The strategic position of Curup as an interregional connecting route accelerated urban development and expanded spatial functions. This developmental process reflects the existence of competition, dominance, and succession that shaped the urban structure and was accompanied by social and cultural adaptations within the community. Therefore, the development of Curup was influenced not only by economic factors but also by historical and social dynamics within the local context. The implications of this study contribute to the fields of urban history and social ecology, particularly in understanding the transformation of market-based cities in local regions. Curup, Urban Ecology, Market, Urban Development, Urban Structure, Social Transformation.